Pengaruh Pelaksanaan Meditasi Pernapasan Terhadap Penurunan Rasa Cemas Pada Penderita Fobia Gelap (Nyctophobia) (Studi Kasus Pada Karyawan CV. Shanghai Kop Relaksasi Mitraraharja) - Valdi Haris; Sutrisno; Surya R. Widya (Sekolah Tinggi Agama Buddha Nalanda, 2020)
This study aims to determine the effect of meditation on helping reduce anxiety in patients with dark phobia (Nyctophobia). This study uses a quasi-experimental research method and the results of the study are presented descriptively with purposive sampling conducted to CV employees. Shanghai Kop Mitraraharja Relaxation which has a dark phobia (Nyctophobia). Based on the results of the study, it was shown that breathing meditation had a good influence in reducing anxiety in patients with dark phobia, in which case the decrease was measured using the HARS (Hamilton Anxiety Rating Scale) questionnaire.